WORKSHOP PEMBELAJARAN BERBASIS HOTS UNTUK MENINGKATKAN KREATIVITAS DAN BERPIKIR KRITIS SISWA - Auliya Wahyuni, Hilyatul; Mamesah, Elly Diana; Basri, Hasan (Universitas Islam 45 Bekasi, 2025)
The Higher Order Thinking Skills workshop was conducted at SDN Muktijaya 03, Setu District, Bekasi Regency, as an effort to enhance students’ creativity and critical thinking through strengthening teacher competencies. The main issue addressed was the limited understanding of teachers in designing learning activities that stimulate higher-order thinking, resulting in classroom practices that often emphasize memorization and basic skills. The implementation method consisted of three stages, namely the introduction of higher-order thinking concepts, training in the development of higher-order thinking–based questions, and implementation and evaluation using the interactive Wordwall platform. Throughout the training, teachers were guided to design questions that foster analysis, evaluation, and creation, while also integrating instructional strategies suited to different learning styles. The results revealed a significant improvement in teachers’ understanding of higher-order thinking and their ability to construct relevant questions, although challenges remained regarding time allocation and the complexity of question design. The evaluation further demonstrated that the use of higher-order thinking–based questions increased student engagement in the learning process and encouraged the development of creativity and critical thinking. The conclusion of this program highlights that the workshop proved effective in strengthening teachers’ pedagogical understanding and provided alternative technology-based learning strategies, making it highly relevant to be applied sustainably in order to support the quality of education at the elementary school level.